KAJIAN MACAM PUPUK KANDANG DAN KONSENTRASI ELISITOR BIOSAKA TERHADAP PERTUMBUHAN DAN HASIL KUBIS (Brassica oleraceae L): elisitor biosaka, kubis, pupuk kandang - Fathul Huda; Siswadi; Sigit Saputro, Avisema (innofarm, 2024)
Research on "Study of Various Manures and Biosaka Elicitor Doses on the Growth and Yield of Cabbage (Brassica oleracea L)" was conducted from March 2024 to June 2024 in Kadipekso Hamlet, Gumeng Village, Jenawi, Karanganyar, at an altitude of Â± 1456 meters above sea level. The study aimed to determine the interaction of the appropriate concentration of Biosaka elicitor application on the growth and yield of cabbage plants. The research method used was a factorial approach with a Completely Randomized Block Design (CRBD), consisting of two factors and three replications. The research factors were Manure and Biosaka Elicitor. The observed parameters included Plant Height, Leaf Diameter, Leaf Color Chart (LCC), Number of Leaves, Number of Crop Leaves, Plant Diameter, and Cabbage Plant Weight. The results were analyzed using a 5% ANOVA test. The study showed that the application of different Manure Concentrations had a significant effect on Plant Height, Leaf Diameter, Leaf Color Chart (LCC), Number of Leaves, Number of Crop Leaves, Plant Diameter, and Cabbage Plant Weight. The application of Biosaka Elicitor doses had a significant effect on Plant Height, Leaf Diameter, Leaf Color Chart (LCC), Number of Leaves, Number of Crop Leaves, Plant Diameter, and Cabbage Plant Weight. The interaction between Manure and Biosaka Elicitor had a significant effect on Plant Height, Plant Diameter, Leaf Color Chart (LCC), Number of Leaves, Number of Crop Leaves, and Plant Diameter, but no significant effect on Cabbage Plant Weight. The best concentration of Manure and Biosaka Elicitor was found with cow manure and 45ml/l Biosaka Elicitor.